»This Large Jewish Mass Striding with Fatal Tranquility towards Its Doom«: The Poetic and Political Jewish Illusions in Naomi Frankel's Saul and Joanna - Levin, Orna (Jewish studies quarterly, 2019)
The focus of this study is on the collective self-delusion constructed by the Jews in regard to their fate under the Nazi regime and in regard to the Zionist mission, as it emerges in Naomi Frankel's trilogy Saul and Joanna. I explore Frankel's use of the characters' illusion as a literary construct, in her writing about the Holocaust only a decade after the Second World War, which shows Frankel to be a unique writer in the cultural milieu that surrounded her. To examine the way in which their self-delusion vis-à-vis the Zionist mission is revealed in the literary work, I rely on the theory of the political unconscious, a concept derived from Frederick Jameson's cultural worldview. The fact that the trilogy was well accepted by the literary critics of the time highlights the importance of re-examining this work 60 years after the publication of the first volume of the trilogy.